A Cross-Sectional Study of Chest Wall Development in Patients with Pectus Excavatum - Chang, Pei-Yeh; Zeng, Qi; Wong, Kin-Sun; Lai, Jin-Yao; Chen, Jeng-Chang; Wang, Chao-Jan; Chang, Chee-Jen (The Thoracic and Cardiovascular Surgeon, 2015)
Background We conducted a cross-sectional study to quantify the developmental changes of the thoracic cage in patients with pectus excavatum (PE).Methods The preoperative posteroanterior standing chest radiographs (chest PAs) of 1,197 consecutive patients with PE, together with 1,661 age- and sex-matched minor surgery patients, as a control group, who were seen between June 2005 and February 2013, were reviewed. The maximum width of each rib pair and chest height (H) were measured on the chest PA.Results In the PE group, the normal thoracic contour in younger patients was replaced by a characteristic can-shaped chest wall, which showed protrusion of the upper ribs, an increased H, and a straightened lateral border of the chest cage, as they grew into adulthood. The chest height difference between the PE and control groups increased progressively, from the age of 8 years and most significantly from age 13 to 17 years. No difference was observed in the middle and lower rib widths. Sex did not influence these trends.Conclusion The PE chest wall shows a significant increment in chest height, and upper rib width starts during the period of rapid growth and is maintained into adulthood. The thoracic deformity in patients with PE includes more than just the sternal deformity.
Keywords: chest wall; growth; chest radiology; pectus excavatum